The Influence of Human Resource Competence and Information Technology Utilisation on the Accuracy of Treasurer Accountability Reporting in the Jayapura Regency Government - A. Ahmad; Siti Rofingatun; Quincy F. Kambuaya; Paulus K. Allo Layuk; Risky Novan Ngutra; Alfiana Antoh (Golden Ratio of Data in Summary, 2026)
This study analyses the influence of human resource competence and information technology utilisation on the accuracy of treasurer accountability reporting in the Jayapura Regency Government, as well as testing the role of organisational commitment as a moderating variable. The study uses a quantitative approach with an explanatory survey design. A sample of 160 respondents was determined using the Slovin formula, and data was collected through questionnaires administered to regional financial management officials/employees. Analysis was performed using multiple linear regression and interaction (moderation) tests with the aid of statistical software. The results show that human resource competence has a positive and significant effect on the accuracy of treasurer accountability reporting (p<0.05), and the use of information technology also has a positive and significant effect (p<0.05). Simultaneously, both variables have a significant effect on reporting accuracy (p<0.05).